Vitamin D deficiency in pediatric patients using antiepileptic drugs: systematic review with meta‐analysis - Cíntia Junges; Tania Diniz Machado; Paulo Ricardo Santos Nunes Filho; Rudimar Riesgo; Elza Daniel de Mello (Brazilian Society of Pediatrics, 2020)
Objectives: To measure the prevalence of vitamin D deficiency (through the 25‐hydroxyvitamin D metabolite) in pediatric patients using antiepileptic drugs. Source of data: Meta‐analysis of studies identified through search in the PubMed, Embase, LILACS, and Cochrane Library databases, on February 19, 2019. Summary of data: A total of 748 articles were identified, 29 of which were relevant to the objectives of this study. The prevalence of vitamin D deficiency found was 0.32 (95% CI = 0.25 ‐ 0.41; I2 = 92%, p < 0.01). In the subgroup analyses, the most significant results were observed in the group of patients using cytochrome P450‐inducing antiepileptic drugs, with a prevalence of 0.33 (95% CI = 0.21 ‐ 0.47; I2 = 86%, p < 0.01) and, considering the study design, in the subgroup of cohort studies, with a prevalence of 0.52 (95% CI = 0.40 ‐ 0.64; I2 = 76%, p < 0.01). Conclusions: Taking into account the deleterious effects of vitamin D deficiency on the bone health of individuals using antiepileptic drugs, it is suggested to include in their care 25‐hydroxyvitamin D monitoring, cholecalciferol supplementation, and treatment of the deficiency, when present. Resumo: Objetivos: Mensurar a prevalência de deficiência de vitamina D (através do metabólito 25‐hidroxivitamina D) em pacientes pediátricos em uso de fármacos antiepilépticos. Fonte dos dados: Metanálise de estudos identificados por meio de pesquisa nas bases de dados Pubmed, Embase, LILACS e Cochrane em 19 de fevereiro de 2019. Síntese dos dados: Foram identificados 748 artigos, dos quais 29 mostraram‐se relevantes aos objetivos deste estudo. A prevalência de deficiência de vitamina D encontrada foi de 0,32 (IC 95% = 0,25-0,41) (I2 = 92%, p < 0,01). Nas análises por subgrupos, os resultados mais expressivos foram observados no grupo de pacientes em uso de fármacos antiepilépticos indutores do citocromo P450, que apresentou prevalência de 0,33 (IC 95% = 0,21-0,47) (I2 = 86%, p < 0,01). Considerou‐se o delineamento dos estudos, no subgrupo de estudos de coorte, com prevalência de 0,52 (IC 95% = 0,40-0,64) (I2 = 76%, p < 0,01). Conclusões: Levando‐se em consideração os efeitos deletérios da deficiência de vitamina D na saúde óssea dos sujeitos em uso de fármacos antiepilépticos, sugere‐se incluir em seu atendimento, o monitoramento de 25‐hidroxivitamina D, suplementação com colecalciferol e tratamento de deficiência quando existente.